Influence of Maternal Region of Birth on Placental Pathology of Babies Born Small - Mindi Fernando; Nalin Choudhary; Beena Kumar; Natasha Juchkov; Kathryn Shearer; Stacey J. Ellery; Miranda Davies-Tuck; Atul Malhotra (Children, 2022)
Background: Placental pathology is a common antecedent factor in infants born small for gestational age. Maternal region of birth can influence rates of SGA. Aims: To determine the association of maternal region of birth on placental pathology in babies that are born small, comparing a South Asian born population with Australia and New Zealand born women. Materials and methods: A retrospective cohort study was conducted at Monash Health, the largest public health service in Victoria. Mother-baby pairs above 34 weeks’ gestation and birth weight less than 10th centile born in 2016 were included. Placental pathology reports and medical records were reviewed. Statistical analyses of placental and selected neonatal outcomes data were performed. Results: Three hundred and eleven small for gestational age babies were included in this study, of which 171 were born to South Asian mothers and 140 to Australian and New Zealand mothers. There were no significant differences in gestational age at birth between the groups (38.7 (1.6) vs. 38.3 (1.7) weeks, p = 0.06). Placental pathology (macroscopic and microscopic) data comparisons showed no significant differences between the two groups (81% major abnormality in both groups). This was despite South Asian small for gestational age babies being less likely to require admission to a special care nursery or neonatal intensive care unit (35 vs. 41%, p = 0.05), or have a major congenital abnormality (2.3 vs. 4.3%, p = 0.04). Conclusion: In this observational study, maternal region of birth did not have an influence on placental pathology of babies born small, despite some differences in neonatal outcomes.